Review of the genus Phyllotrella Gorochov, with descriptions of three new species from China (Orthoptera: Gryllidae: Podoscirtinae: Podoscirtini) - Sun, Kai; Liu, Hao-Yu (Zootaxa, 2019)
Three new species of Phyllotrella Gorochov, 1988 are described: P. hainanensis sp. nov. (China: Hainan), P. transversa sp. nov. (China: Guangdong, Guangxi) and P. fumingi sp. nov. (China: Guangdong), which are illustrated with the habitus, metanotal gland, phallus and anal plate of the male. P. planidorsalis Gorochov, 1988 is excluded from Chinese fauna. A distribution map and a key of all species of Phyllotrella are provided.